2011
DOI: 10.1080/14786435.2010.536176
|View full text |Cite
|
Sign up to set email alerts
|

Identification of finite shear-elasticity in the liquid state of molecular and polymeric glass-formers

Abstract: Finite shear elasticity has been identified in the liquid state. The study is expanded to a van der Waal's molecular glass-former, o-terphenyl, and to an ordinary polymer melt, polybutylacrylate, as a function of their molecular weight. These fluids exhibit shear elasticity at the sub-millimetre scale and far above any phase transition. This macroscopic property challenges the conventional terminal relaxation modes (-process or terminal viscoelastic times (reptation)) in terms of individual molecular process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 38 publications
13
44
0
Order By: Relevance
“…We reveal in all cases, a weak but non-ambiguous solid-like low frequency response at weak shear strain solicitation. The present work thus extends, details and generalizes the identification of solid-like correlations previously reported above the melting point, of glycerol [4], of o-terphenyl [5], of polypropylene glycol [3] and more generally in polymer melts [1,3].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…We reveal in all cases, a weak but non-ambiguous solid-like low frequency response at weak shear strain solicitation. The present work thus extends, details and generalizes the identification of solid-like correlations previously reported above the melting point, of glycerol [4], of o-terphenyl [5], of polypropylene glycol [3] and more generally in polymer melts [1,3].…”
Section: Introductionsupporting
confidence: 61%
“…However, several recent results have revived the assumption of long-range elastic correlations and therefore of long time scales, hitherto neglected in the liquid state even away from any phase transition. The measurement of macroscopic finite shear elasticity at the sub-millimeter scale has been essentially enabled by minoring the disturbance of the liquid during the mechanical solicitation and by improving the boundary conditions of the liquid to the substrate [1][2][3][4][5]. This method was successfully applied to glass formers (polymer melts, polypropylene glycol, o-terphenyl, glycerol) revealing in the low frequency range (typically 10 − 2 -10 2 rad/ s), a finite shear modulus and a finite viscous modulus.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, L. Noirez and co-authors reported on elastic behaviors in the isotropic phase of SCLCPs using a conventional rheometer and at the millimeter scale [14]. Then, solid-like behaviors (G′ and G″ constant with G′ > G″) were identified using the total wetting protocol [28] in various glass formers (glycerol, o-terphenyl) and ordinary polymers [29][30][31][32]. In 2007, S-Q Wang [55] reproduced the results of [15] using the same protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the shear-induced phase has thus to be related to a cohesive property hitherto neglected in the isotropic phase. Since 2005, we have been working on, and demonstrating, that improved dynamic measurements enable access to this cohesive property via the identification of a low frequency shear elasticity (solid-like character) in the liquid state in various glass formers away from any phase transition [28][29][30][31][32]. We apply this improved protocol first to the isotropic phase of the SCLCP, PANO2, compare it to an ordinary polymer chain (polybutylacrylate melt (PBuA)) of the same degree of polymerization, and finally examine the case of a short alkyl chain assimilated to a spacer: The heptadecane.…”
Section: Figurementioning
confidence: 99%
“…Recent experimental developments have shown that reinforcing the surface contacts using high energy surface improves the measurement of the dynamic response [14][15][16][17][18][19][20][21]. When the liquid molecules are strongly in interaction with the surface, the noise observable at low frequency grows and forms a well-defined signal, stronger than the viscous response (Fig.…”
Section: The Key Role Of the Surface In Dynamic Relaxation Measurementsmentioning
confidence: 99%